Kesiapan Guru Mengimplementasikan Kurikulum 2013: Studi Pada Sekolah Dasar Pilotting - Zuryanty Zuryanty (Universitas Negeri Padang, 2019)
This study aims to find out and measure 4 model factors that influence the readiness of elementary school teachers in implementing the 2013 curriculum. This research is a correlation study. The data used is quantitative data. The technique used is confirmatory factor analysis and partial correlation. This study shows that the four-factor model as a suitable and very significant indicator variable correlates with the readiness of primary school teachers in implementing the 2013 curriculum. This study confirms that the transformation of mindsets, understanding of 2013 curriculum concepts, ability to analyse the subject matter and teaching design are significantly suitable and relates positive to the readiness of primary school teachers as latent variables.